Teachers' Interpersonal Communication for Internalizing Islamic Values Against Verbal Bullying - Mu’adz Haidar Zulkarnain; Agus Pahrudin; Achi Rinaldi; Ali Murtadho (Ahlussunnah: Journal of Islamic Education, 2026)
Verbal bullying in elementary schools remains a persistent problem that is often overlooked as a normal aspect of children's social interaction, despite its potential psychological and socio-emotional consequences. This study aims to examine how teachers’ interpersonal communication strategies facilitate the internalization of Islamic values in addressing verbal bullying among elementary school students. A qualitative case study design was employed in an Islamic elementary school in West Java, Indonesia. Data were collected through participant observation, in-depth interviews, and document analysis involving four teachers and nine students. Data were analyzed using the Miles, Huberman, and Saldaña interactive model, including data condensation, data display, and conclusion drawing. The findings reveal three interconnected communication strategies; i) preventive communication through role modeling (uswah hasanah) and greeting habituation; ii) responsive communication through gentle speech (qawlan layyinan) and empathetic dialogue; and iii) restorative communication through personal advice (mau‘izah hasanah) and the reinforcement of brotherhood values (ukhuwwah). These strategies facilitated the internalization of Islamic values such as rahmah (compassion), ‘iffah al-lisan (ethical speech), and ta‘āwun (mutual assistance), which contributed to reducing verbal bullying tendencies and strengthening students’ awareness of respectful communication. This study contributes to the literature on Islamic educational communication by proposing a value-based interpersonal communication framework for bullying prevention and intervention in elementary school settings.